ACADEMIC WRITING AND ITS DEVELOPMENT IN RUSSIA: GENRE APPROACH - T. В. Alenkina (Moscow Polytechnic University, 2018)
While in Anglo-American universities the course traditionally called as "English Composition" has been in the curriculum for a long time, in Russia "Academic Writing" has been actively developing only for the last 10-15 years. Nowadays Academic Writing is taught in many universities all over Russia, writing centers are set up, annual international conferences are held. In the focus of Russian teachers and researchers are the genres of academic writing which are important and interesting for students (e.g., essay, letter of recommendation, grant proposal etc), thus the genre approach is being applied. For the last five years with the development of the concept of "education through research" there has been an increasing role of the professionally-targeted genres. Special attention is paid to rendering as "writing-transformation" forming the linguoprofessional competence of students. The shift from writing as product to writing as process and practice signifies a different, independent status of writing. The search for the system approach to genre teaching is still ahead.